2018
DOI: 10.1186/s40360-018-0248-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of self-medication in Ethiopia: a systematic review and meta-analysis of observational studies

Abstract: BackgroundSelf-medication is the use of drugs to treat self-diagnosed disorders and/or symptoms, or the intermittent or continued use of a prescribed drug for recurrent disease or symptoms. This phenomenon is alarmingly increasing over time despite the occurrence of health-related hazards. This study is, therefore, aimed to quantitatively estimate self-medication practice and possible reasons for it in Ethiopia.MethodsData were identified from major databases and indexing services including EMBASE (Ovid), PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 41 publications
2
60
1
6
Order By: Relevance
“…This finding was correlated with previous reports done in different areas. 2,8,9,13,19,22,27 This means that HCPs particularly physicians had imposed their subjective judgment in determining both their diagnosis and treatment. 8,22,45 Indeed, it has been observed that HCPs get access to medication as well as their knowledge of drug use is a major reason for the high rate of the SMPs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding was correlated with previous reports done in different areas. 2,8,9,13,19,22,27 This means that HCPs particularly physicians had imposed their subjective judgment in determining both their diagnosis and treatment. 8,22,45 Indeed, it has been observed that HCPs get access to medication as well as their knowledge of drug use is a major reason for the high rate of the SMPs.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) defined self-medication (SM) as "the use of drugs to treat self-diagnosed diseases or symptoms, or the intermittent or continued use of a prescribed drug for chronic or recurrent disease or symptoms". [1][2][3] SM as one element of self-care involves the process of getting and consuming drugs without the advice of a physician either for diagnosis, treatment, prescription, surveillance or monitoring. [4][5][6][7][8][9] It is also associated with the selection, procurement and use of medicines by individuals to treat self-diagnosed conditions as well as giving medications to other household members or dependent.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations